French Grammatical Accents: Practices, Sociolinguistic Foundations, and Pedagogical Implications in a Multilingual Setting - Antoine Willy Ndzotom Mbakop; Sonia Laurei Emalieu Kanko; Adrienne Michelle Tida (National Research University Higher School of Economics, 2018)
The present paper probes the use of French grammatical accents by English-speaking learners of French in a multilingual country: Cameroon. Its aim is twofold. First, it highlights the extent to which the various appropriative uses of French by French-speaking Cameroonians influence the form of the language spoken by their English-speaking counterparts. Then, it checks the effect of the language spoken by these learners on their written language. The data were collected among 160 Form 3 and Form 4 pupils from two high schools in the town of Maroua, Far North Region, Cameroon. Six tests and fifty tape recordings were carried out among the target population. Also, four French teachers were tape recorded during the exercise. The analysis of the errors made by the informants revealed significant patterns of acute and grave accents in the spoken language of respondents. These patterns of oral usage were found to strongly correlate with their written production. It therefore appears that Cameroon French displays some specific phonological characteristics, which severely spoils the acquisition of grammatical accents by English-speaking Cameroonians. These findings may revive the debate over whether French in former colonies should adapt to its contexts or keep its native purity.